A Reduced-Order Model of Lithium–Sulfur Battery Discharge - Noushin Haddad; Hosam K. Fathy (Batteries)
This paper examines the problem of modeling lithium–sulfur (Li-S) battery discharge dynamics. The importance of this problem stems from the attractive specific energy levels achievable by Li-S batteries, which can be particularly appealing for applications such as aviation electrification. Previous research presents different Li-S battery models, including “zero-dimensional” models that neglect diffusion while using the laws of electrochemistry to represent reduction–oxidation (redox) rates. Zero-dimensional models typically succeed in capturing key features of Li-S battery discharge, including the high plateau, low plateau, and dip point visible in the discharge curves of certain Li-S battery chemistries. However, these models’ use of one state variable to represent the mass of each active species tends to furnish high-order models, with many state variables. This increases the computational complexity of model-based estimation and optimal control. The main contribution of this paper is to develop low-order state-space model of Li-S battery discharge. Specifically, the paper starts with a seventh-order zero-dimensional model of Li-S discharge dynamics, analyzes its discharge behavior, constructs phenomenological second- and third-order models capable of replicating this behavior, and parameterizes these models. The proposed models succeed in capturing battery discharge behavior accurately over a wide range of discharge rates. To the best of our knowledge, these are two of the simplest published models capable of doing so.